The Missing Type: Where Are the Inequality Averse (Students)? - Thomas Epper; Julien Senn; Ernst Fehr (Center for Economic Studies and ifo Institute (CESifo), 2024)
The empirical evidence on the existence of social preferences—or lack thereof—is predominantly based on student samples. Yet, knowledge about whether these findings can be extended to the general population is still scarce. In this paper, we compare the distribution of social preferences in a student and in a representative sample. Using descriptive analysis and a rigorous clustering approach, we show that the distribution of the general population's social preferences fundamentally differs from the students' distribution. In the general population, three types emerge: an inequality averse, an altruistic, and a selfish type. In contrast, only the altruistic and the selfish types emerge in the student population. The absence of an inequality averse type in the student population is particularly striking considering the fact that this type comprises about 50 percent of the individuals in the general population sample. Using structural estimation, we show that differences in age and education are likely to explain these results. Younger and more educated individuals—which typically characterize students— not only tend to have lower degrees of other-regardingness but this reduction in other-regardingness basically nullifies behindness aversion among students. Differences in income, however, do not seem to affect social preferences. These findings provide a new cautionary tale that insights from student populations might not extrapolate to the general population.
Keywords: C80; C90; D30; D63; 330; social preferences; altruism; inequality aversion; preference heterogeneity; subject pools; sample selection